Land use change drivers in the Hyrcanian Vegetation Area: Dynamic simultaneous equations system with panel data approach. (December 2020) - Jahanifar, Komeil; Amirnejad, Hamid; Mojaverian, Seyed Mojtaba; Azadi, Hossein
Highlights: This study aimed to identify the variables that impact the land use change from 1997 to 2017. The results showed that in all scenarios, economic drivers played the main role. Social drivers played a significant role in conversion of the agricultural land and rangelands into residential areas. Ecological drivers have had the least impact on land use change. Based on the results over the 20-year period, agricultural and residential lands have increased. Abstract: This case study has been carried out on the Hyrcanian Vegetation Area (HVA) located in Northern Iran. The current study aimed to identify the drivers and variables that have been effective in the land use changes (LUCs) of forests, rangelands, agricultural lands, and residential areas from 1997 to 2017 in 14 townships. For this purpose, satellite images are prepared and after the processing, the level of change is determined by using the Geospatial monitoring and modeling system. In the following, the level of LUCs along with economic, social, ecological, and legal drivers in the form of a simultaneous equation system was estimated by Two-Stage Least Square (2SLS) estimator. LUCs' results showed that the forest in 1997 was about 623529 ha, and it decreased by 618419 ha in 2017. In addition, the rangeland at the beginning of the period was 914780 ha, and in the end, it reached about 906103 ha. Satellite images showed that about 183592 ha of forests were converted into agricultural lands and about 276091 ha to residential areas. Moreover, in rangelands, 56035 ha of them have been farmed, and about 197894 ha have been changed to residential areas. Furthermore, the results stated that in all scenarios of changes, economic drivers such as income per capita, inflation, and products relative price played the main role. Moreover, social drivers play a significant role in changing the agricultural land and rangeland to residential areas. Factors such as population and the demand for food and housing show that the importance of this issue is more than ever before. Unfortunately, ecological drivers have unexpectedly had the least impact on LUCs. As a result, it is recommended to minimize the cost of agricultural inputs and adjust the market price of products considering the inflation rate. Moreover, population adjustment policies should also be considered to reduce the growing population pressure. Finally, the government should play a more effective role in protecting lands and preventing their change of use. This should be done through making fair distribution policies on wealth, applying the provision of funds and the long-term return to low-income farmers, strengthening the income sources of residents, and by developing and equipping protection units.